Photobiomodulation 30 min or 6 h Prior to Cycling Does Not Alter Resting Blood Flow Velocity, Exercise-Induced Physiological Responses or Time to Exhaustion in Healthy Men - Dutra, Yago Medeiros; Claus, Gabriel Machado; Malta, Elvis de Souza; Seda, Daniela Moraes de Franco; Zago, Anderson Saranz; Campos, Eduardo Zapaterra; Ferraresi, Cleber; Zagatto, Alessandro Moura (Frontiers in Physiology, 2021)
Purpose: The aim of the current study was to investigate the effects of photobiomodulation therapy (PBMT) applied 30 minutes or 6 hours prior to cycling on blood flow velocity and plasma nitrite concentrations at rest, time to exhaustion, cardiorespiratory responses, blood acid-base balance, and K+ and lactate concentrations during exercise. Methods: In a randomized, crossover design, 13 healthy untrained men randomly completed four cycling bouts until exhaustion at the severe-intensity domain (i.e., above respiratory compensation point). Thirty minutes or 6 hours prior to the cycling trials, participants were treated with PBMT on the quadriceps, hamstrings, and gastrocnemius muscles of both limbs using a multi-diode array (11x30 cm with 264 diodes) at doses of 152 J or a sham irradiation (with device turned off, placebo). Blood samples were collected before and 30 minutes or 6 hours after treatments to measure plasmatic nitrite concentrations. Doppler ultrasound exams of the femoral artery were also performed at the same time points. Cardiorespiratory responses, blood acid-base balance, and K+ and lactate concentrations were monitored during exercise sessions. Results: PBMT did not improve the time to exhaustion (p=0.30). At rest, no differences were found in the peak systolic velocity (p=0.97) or pulsatility index (p=0.83) in the femoral artery, and in plasma nitrite concentrations (p=0.47). During exercise, there were no differences for any cardiorespiratory response monitored (heart rate, p=0.15; oxygen uptake, p=0.15; pulmonary ventilation, p=0.67; carbon dioxide output, p=0.93; and respiratory exchange ratio, p=0.32), any blood acid-base balance indicator (pH, p=0.74; base excess, p=0.33; bicarbonate concentration, p=0.54), or K+ (p=0.22) and lactate (p=0.55) concentrations. Conclusions: PBMT at 152 J applied 30 minutes or 6 hours before cycling at severe-intensity did not alter resting plasma nitrite and blood flow velocity in the femoral artery, exercise-induced physiological responses, or time to exhaustion in healthy untrained men.